Implementation Of Electrocatalytic Reactor As Oxidation Unit For Residual Reagent Wastewater Of Testing Laboratory - Aris Mukimin; Kukuh Aryo Wicaksono; Nur Zen; Agus Purwanto; Hanny Vistanti (Balai Besar Standardisasi dan Pelayanan Jasa Pencegahan Pencemaran Industri, 2018)
The remaining reagent from the sample analysis process become a significant source of hazardous waste of laboratory tasting activities. Methylene blue, phenol and oil are pollutants common in the remaining reagent waste. The electrocatalytic reactor is effective oxidation units for these organic pollutants. The reactor was made for a 50 L capacity with cylindrical metal oxide as the anode. The three anode which 6 cm in diameter and 50 cm in length were paired stainless cathode with the distance of 2.5 cm. The reactor was also equipped with a stirrer that is connected to the motor so that the mass transfer and oxidizing agents is more effective. The reactor application was carried out by feeding the remaining reagent waste into the electrocatalytic unit and giving DC potential 5 Volt. Each COD content for reagent waste of detergent: 2864 mg/L, phenol: 838 mg/L and oil: 708 mg/L. The reactor has reduced COD to 2157 mg/L (detergent), 399 mg/L (phenol) and 506 mg/L (oil) for 120 minutes. The high COD content in residual is caused by solvent (chloroform or hexane) that used at extraction step in determining the process of a sample. This compound is tough to oxidize into CO2 by OH radical or hypochlorite acid formed at the anode during the electrolysis process